2012
DOI: 10.1007/s10765-012-1329-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pressure on Moisture Diffusion in Polymer Matrix Composites

Abstract: Temperature and humidity play a significant role in the mechanical behavior and long-term durability of polymer matrix composites (PMCs). Several standard test methods including some accelerated test methods involving higher temperatures and pressures are available for environmental qualification of these PMCs. While the effect of temperature on humidity diffusion has been studied extensively, the effect of pressure has received less attention. This study seeks to interrogate the effect of pressure on diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The pressure of the environment also affected the moisture diffusion behavior in PMCs. It was found that the time to saturation and the saturation moisture content increased with the pressure in the environmental chamber [12].…”
Section: Introductionmentioning
confidence: 99%
“…The pressure of the environment also affected the moisture diffusion behavior in PMCs. It was found that the time to saturation and the saturation moisture content increased with the pressure in the environmental chamber [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the flow velocity has an impact on the humidity absorption procedure: Davis et al [18] approved that the increase in the flow velocity causes an increment in the diffusion coefficient. As far as, Pilli et al[19] and Humeau et al [20] showed that the raise in the flow velocity induces the humidity diffusion phenomena acceleration. The research of Zhang et al [21] revealed that using the obtained regression equation, the temperature has a high influence on the diffusion process, especially for diffusion velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Anomalous water diffusion through polymers were often reported, and water diffusion coefficients could be affected by many factors. These factors may include testing temperatures, glass transition temperature, moisture concentration, types of fillers, mechanical stress and pressure, polymer relaxation, and chemical interactions . Usually, Fickian models are too simple to fully model the complex moisture diffusion in polymers.…”
Section: Introductionmentioning
confidence: 99%